Utilisation of Organic Waste as Bioethanol Raw Material with Variation of Yeast Concentration (Saccharomycess Cerevisiae) - Lubis, Mhd Afnan Yogi; Tanggasari, Devi (Universitas Muhammadiyah Mataram, 2024)
In the midst of demands to reduce dependence on fossil energy sources that are decreasing, this research was conducted as an effort to make bioethanol as an alternative energy source. The purpose of this study was to determine the effect of yeast variation on pH and bioethanol content. This research was conducted using the method of Completely Randomised Design (CRD) factorial pattern involving one main factor, namely yeast variation with three replicates for each treatment. Parameters in this study are pH testing and bioethanol content. The best results of both peremeter is the best pH contained in the 3rd treatment with an average amount of 4.84, in testing the bioethanol content of the best value contained in the 3rd treatment with the amount of yeast 6 grams of ethanol content average 0.9%. It can be concluded that bioethanol content is influenced by yeast, distillation, and fermentation time. the higher the yeast, the higher the pH, alcohol density, and yield produced.